Study on fabrication of arrays of NdFeB magnetic microstructures using ink-jet printer - Lê Việt Cường (Journal of Military Science and Technology, 2022)
In this study, square-shaped magnetic microstructures with a surface area of 500×500 mm2 and a thickness of 40 mm were fabricated in an order by an ink-jet printer. A printing solution contains NdFeB hard magnetic particles with a remanent magnetization (MR) 47 emu/g and a coercivity force (HC) 2.0 kG. Although results present that the microstructures after magnetized by an external magnetic field 20 kG have MR 0.16 emu/g and HC 820 G due to a low content of NdFeB particles in the printing solution, the microstructures are capable of attracting Fe3O4 magnetic particles. The analysis results of magnetic induction component (Bz) and its gradient in the direction perpendicular to the surface of the microstructures (dBz/dz) as well as in the direction parallel to the surface of the microstructure (dBz/dy) show that the microstructures have a possibility to separate magnetic objects based on weight.